Chelation efficacy and erythroid response during deferasirox treatment in patients with myeloproliferative neoplasms in fibrotic phase. (18th September 2015) - Latagliata, Roberto; Montagna, Chiara; Porrini, Raffaele; Di Veroli, Ambra; Leonetti, Sabrina Crescenzi; Niscola, Pasquale; Ciccone, Fabrizio; Spadea, Antonio; Breccia, Massimo; Maurillo, Luca; Rago, Angela; Spirito, Francesca; et al.
Abstract: At present, very few data are available on deferasirox (DFX) in the treatment of patients with Philadelphia‐negative myeloproliferative neoplasms in fibrotic phase (FP‐MPN) and transfusion dependence. To address this issue, a retrospective analysis of 28 patients (22 male and 6 female) with FP‐MPN and iron overload secondary to transfusion dependence was performed, based on patients enrolled in the database of our regional cooperative group who received treatment with DFX. DFX was started after a median interval from diagnosis of 12.8 months (IR 7.1–43.1) with median ferritin values of 1415 ng/mL (IR 1168–1768). Extra‐hematological toxicity was reported in 16 of 28 patients (57.1%), but only two patients discontinued treatment due to toxicity. Among 26 patients evaluable for response (≥6 months of treatment), after a median treatment period of 15.4 months (IR 8.1–22.3), 11 patients (42.3%) achieved a stable and consistent reduction in ferritin levels <1000 ng/mL. As for hematological improvement, 6 of 26 patients (23%) showed a persistent (>3 months) rise of Hb levels >1.5 g/dL, with disappearance of transfusion dependence in four cases. Treatment with DFX is feasible and effective in FP‐MPN with iron overload. Moreover, in this setting, an erythroid response can occur in a significant proportion of patients.